The Teachers’ Strategies in Teacing Speaking at SMK Muhammadiyah Prambanan - Hardika, Bunga; Pratolo, Bambang Widi (IKIP Siliwangi, 2025)
Teaching speaking skills is a significant challenge for teachers, especially in a vocational school environment. This study aims to identify the strategies used by teachers in teaching speaking at SMK Muhammadiyah Prambanan. The subjects of this study were three English teachers and 35 eleventh grade students from the Broadcasting class in the 2023/2024 academic year. Using descriptive qualitative method, this study collected data through interviews and classroom observations. The results showed that teachers used a variety of strategies, including storytelling, class discussions, and the use of social media, which effectively improved students' motivation, active participation, and speaking skills. Storytelling engages students emotionally, helping them build vocabulary and public speaking confidence. Class discussions encourage active participation, improving students' communication and critical thinking skills. Meanwhile, social media allows students to practice English in real-life contexts, making learning more interactive and fun. These strategies are proven to not only improve students' speaking ability, but also foster their personal and social development. This comprehensive approach aligns with the demands of the vocational curriculum, preparing students with the essential communication skills needed for professional and social growth.